2017
DOI: 10.1038/cgt.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Association of long non-coding RNA H19 and microRNA-21 expression with the biological features and prognosis of non-small cell lung cancer

Abstract: In recent years, long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have been shown to play important roles in tumor biological function. The aim of this study was to investigate the diagnostic and prognostic value of lncRNA H19 and miR-21 expression in non-small-cell lung cancer (NSCLC). H19 and miR-21 expression was measured in tumor tissues and corresponding non-tumor lung tissues from 200 patients by quantitative reverse transcription polymerase chain reaction. Moreover, the in vitro and in vivo effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Currently, the main treatments for lung cancer include surgical excision, chemotherapy and chest radiotherapy. However, the efficacies of these therapies are limited, and novel approaches are needed to improve patients’ life quality and survival . Recent studies suggest that several lncRNAs are dysregulated in multiple cancers, including lung cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main treatments for lung cancer include surgical excision, chemotherapy and chest radiotherapy. However, the efficacies of these therapies are limited, and novel approaches are needed to improve patients’ life quality and survival . Recent studies suggest that several lncRNAs are dysregulated in multiple cancers, including lung cancers .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, miRNA-221 and miRNA-222 are homologous miRNAs located in tandem, within 1 kb from each other, on human X chromosome [14,15]. Recent studies stated that microRNA-221 and miRNA-222 is aberrantly expressed in various malignancies [16] and was found to be overexpressed in triplenegative breast cancer patients [17]. MiRNA-221 and miRNA-222 are thought to serve as oncomiRs because they inhibit many tumor suppressors [18,19,20,21].…”
Section: Introductionmentioning
confidence: 78%
“…Many studies have shown that lncRNAs were deregulated in lung cancer, such as MALAT1 (NEAT2), 44 , 45 HOTAIR, 46 SOX2-OT, 47 and H19. 48 MALAT1 could be associated with prognostic parameter for poor survival 49 and cell migration 50 in lung cancer cases. Compared with normal lung tissue, the expression of HOTAIR was higher in lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%